CODE MIXING USED BY K-POP LOVERS ON SOCIAL MEDIA - Rabiatul Adawiah; Nasrah Nasrah; Nur Zamzam; Tria AR; Maghfirah S. (Inspiring: English Education Journal, 2023)
Code mixing is a global phenomenon since social media emerged as a communication medium for K-Pop lovers in Indonesia. It happens when a speaker/writer uses two or more languages in an utterance/sentence. This research is aiming to explore the types and reasons for code-mixing. The researchers applied the qualitative method using content analysis. The result shows that there are 12 Korean codes and one English code inserted in Bahasa Indonesia as the major code. Intra-sentential or insertion of other codes in the main code is used dominantly by the participants. Other types such as inter-sentential, phonological change, alternation, and congruent lexicalization are not used since the participant did not have any capacity to combine Korean morphemes with Bahasa Indonesia morphemes. Additionally, the reason for using code mixing is analyzed and shows that the participant wants to show their group identity and to talk about certain topics.